Ubiquitin-dependent regulation of a conserved DMRT protein controls sexually dimorphic synaptic connectivity and behavior - Bayer, Emily A; Stecky, Rebecca C; Neal, Lauren; Katsamba, Phinikoula S; Ahlsen, Goran; Balaji, Vishnu; Hoppe, Thorsten; Shapiro, Lawrence; Oren-Suissa, Meital; Hobert, Oliver (eLife, 2020)
Sex-specific synaptic connectivity is beginning to emerge as a remarkable, but little explored feature of animal brains. We describe here a novel mechanism that promotes sexually dimorphic neuronal function and synaptic connectivity in the nervous system of the nematode Caenorhabditis elegans. We demonstrate that a phylogenetically conserved, but previously uncharacterized Doublesex/Mab-3 related transcription factor (DMRT), dmd-4, is expressed in two classes of sex-shared phasmid neurons specifically in hermaphrodites but not in males. We find dmd-4 to promote hermaphrodite-specific synaptic connectivity and neuronal function of phasmid sensory neurons. Sex-specificity of DMD-4 function is conferred by a novel mode of posttranslational regulation that involves sex-specific protein stabilization through ubiquitin binding to a phylogenetically conserved but previously unstudied protein domain, the DMA domain. A human DMRT homolog of DMD-4 is controlled in a similar manner, indicating that our findings may have implications for the control of sexual differentiation in other animals as well.
Keywords: C. elegans; sexual dimorphism; transcription factor; synapse pruning